1972
DOI: 10.1039/f29726801679
|View full text |Cite
|
Sign up to set email alerts
|

Molecular conformations from magnetic anisotropies

Abstract: A method is developed for determining molecular conformations through analysis of experimental molar Cotton-Mouton constants in conjunction with known anisotropic magnetic susceptibilities and electric polarizabilities for structural groups. Molar Cotton-Mouton constants ( x 1OI6 e.m.u.), and derived interplanar angles, for molecules as solutes in carbon tetrachloride at 20°C are : biphenyl (+ 70, 0") ; 2,2'-bipyridyl (+ 76, 25") ; 9,9'-bianthryl (+ 160, 62") ; 9-phenylanthracene (+ 157, 70") ; 1-phenylnaphtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 1 publication
4
17
0
Order By: Relevance
“…Moreover, the anthracene itself exhibits a slight twist such that the dihedral angle between the exterior rings is 10.48. These structural features parallel those seen in 9,10-diferrocenylanthracene [10] and 9,10-di(3-fluorophenyl)anthracene [9,12] with corresponding dihedral angles of 478 and 878, respectively. Furthermore, the 2,5-dihydroxyphenyl ring is oriented such that the hydroxyl group closer to the anthracene is positioned anti with respect to the ferrocenyl unit.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, the anthracene itself exhibits a slight twist such that the dihedral angle between the exterior rings is 10.48. These structural features parallel those seen in 9,10-diferrocenylanthracene [10] and 9,10-di(3-fluorophenyl)anthracene [9,12] with corresponding dihedral angles of 478 and 878, respectively. Furthermore, the 2,5-dihydroxyphenyl ring is oriented such that the hydroxyl group closer to the anthracene is positioned anti with respect to the ferrocenyl unit.…”
Section: Resultssupporting
confidence: 67%
“…However, reaction of 3 a with HBF 4 unexpectedly yields instead 9-ferrocenyl-10-(2,5-dihydroxyphenyl)anthracene (4) via cleavage of the C9 À C12 bond to generate initially a ferrocenyl-stabilized cation. Treatment of 3 a with sodium hydride and iodomethane yields 1,4-dimethoxy-9-ferrocenyltriptycene (3 c) in high yield but, surprisingly, also leads to fission of the C9 À C12 bond resulting, after methylation, in the formation of 9-hydroxy-9-ferrocenyl-10-(2-hydroxy-5-methoxyphenyl)dihydroanthracene (12), which readily dehydrates on silica to form 9-ferrocenyl-10-(2-hydroxy-5-methoxyphenyl)anthracene (8). The X-ray crystal structures of 3 a, 3 c and 4 are reported.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, 2,2'-bipyridine has been reported to adopt a nonplanar transoid conformation with an interplanar angle of about 208 in organic solvents, whereas it exists in a planar transoid conformation in the solid state. [10] Electronic interactions between the chromophores through intramolecular p-stacking were also observed in the fluorescence spectra of 1 and 3. The two-turn strand 6 has been reported to show a characteristic fluorescence emission at 540 nm that was not observed for the one-turn strand 5, which showed simple pyridine-like emission at 400 nm.…”
Section: Resultsmentioning
confidence: 89%
“…However, dipole moment measurements in organic solvents and in basic solutions indicate a non-planar trans configuration, with a dihedral angle of 20°. [17] This discrepancy has been studied before. As the non-planarity was not due to the lack of electron correlation during the optimization, [63] it has been shown that the solvent-solute interactions lie on the basis for this deviation.…”
Section: Structural Properties Of Polypyridyl Ligandsmentioning
confidence: 92%